Managing behavioural challenge among learners with SEND in Primary Private Schools in Dubai: Teachers’ perspective - Haddad, Mona (2019)
Education is one of the constitutional rights guaranteed by law in the United Arab Emirates (UAE) to all without discrimination. The provisions of the Federal Law No. 29 of 2006, as amended by Federal Law No. 14 of 2009 on the Rights of the Disabled, affirm that this right is guaranteed to persons with disabilities. The most important initiatives adopted by the Ministry of Education (MOE) in this regard are the "School for All" initiative, an initiative to promote the integration of persons with disabilities into public education, this was in conformity with the UN Convention on the Rights of Persons with Disabilities (CRPD) (UN 2006). The study aimed to identify the point of view of the primary teachers about the attitudes and causes of aggressive behavior among SEND students in the primary private schools in Dubai. This study was based on a qualitative research method, using a multi-case approach to provide a precise and adequate picture of the application of the initiative by presenting the views and perspectives of some teachers. The researcher used the descriptive method, where a random stratified sample was selected, and the researcher was selected of the schools surveyed, so that the study was conducted on 200 teachers and TLS (shadow teachers).